Antiplatelet therapy in patients with myocardial infarction without obstructive coronary artery disease. Issue 21 (27th January 2021) - Bossard, Matthias; Gao, Peggy; Boden, William; Steg, Gabriel; Tanguay, Jean-Francois; Joyner, Cam; Granger, Christopher B; Kastrati, Adnan; Faxon, David; Budaj, Andrzej; Pais, Prem; Di Pasquale, Giuseppe; et al.
Abstract : Objective: Approximately 10% of patients with myocardial infarction (MI) have no obstructive coronary artery disease. The prognosis and role of intensified antiplatelet therapy in those patients were evaluated. Methods: We analysed data from the Clopidogrel and Aspirin Optimal Dose Usage to Reduce Recurrent Events–Seventh Organisation to Assess Strategies in Ischaemic Symptoms trial randomising patients with ACS referred for early intervention to receive either double-dose (600 mg, day 1; 150 mg, days 2–7; then 75 mg/day) or standard-dose (300 mg, day 1; then 75 mg/day) clopidogrel. Outcomes in patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) versus those with obstructive coronary artery disease (CAD) and their relation to standard-dose versus double-dose clopidogrel were evaluated. The primary outcome was cardiovascular (CV) death, MI or stroke at 30 days. Results: We included 23 783 patients with MI and 1599 (6.7%) with MINOCA. Patients with MINOCA were younger, presented more frequently with non-ST-segment elevation MI and had fewer comorbidities. All-cause mortality (0.6% vs 2.3%, p=0.005), CV mortality (0.6% vs 2.2%, p=0.006), repeat MI (0.5% vs 2.3%, p=0.001) and major bleeding (0.6% vs 2.4%, p<0.0001) were lower among patients with MINOCA than among those with obstructive CAD. Among patients with MINOCA, 2.1% of patients in the double-dose clopidogrel group and 0.6% in the standard-dose group experienced a primary outcome (HR 3.57, 95% CI 1.31 to 9.76), whereas in those with obstructive CAD, rates were 4.3% and 4.7%, respectively (HR 0.91, 95% CI 0.80 to 1.03; p value for interaction=0.011). Conclusions: Patients with MINOCA are at lower risk of recurrent CV events compared with patients with MI with obstructive CAD. Compared with a standard clopidogrel-based dual antiplatelet therapy (DAPT) regimen, an intensified dosing strategy appears to offer no additional benefit with a signal of possible harm. Further randomised trials evaluating the effects of potent DAPT in patients with MINOCA are warranted. Trial registration number: NCT00335452 .